KONTRUKSI MASKULINITAS DAN SUBKULTUR KEKERASAN (STUDI KRIMINOLOGIS ATAS FENOMENA "BUSUR" DI KALANGAN REMAJA KOTA MAKASSAR) - Hairul Saleh Satrul (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study aims to examine the phenomenon of juvenile violence using homemade arrows (busur) in Makassar City through criminological and sociological lenses. The high rate of street crime poses a serious threat to urban community security. This research employs a literature review method by collecting secondary data from various journal articles, textbooks, legal documents, and police reports. The analysis results indicate that this phenomenon is rooted in the distortion of local wisdom Siri' Na Pacce, which is misinterpreted as a justification for communal revenge. Additionally, the construction of hegemonic masculinity drives adolescent boys to prove their bravery through physical aggression and the use of homemade weapons. This subculture of violence is further reinforced by urban spatial segregation ("anak lorong"), the ease of weapon assembly, and widespread provocation via social media. The conclusion of this study emphasizes that repressive law enforcement approaches are insufficiently effective due to the constraints of the Juvenile Criminal Justice System Law (SPPA). The implication is that holistic social policy engineering, such as optimizing the Jagai Anakta program and providing vocational spaces, is required to reintegrate adolescents into conventional and positive social bonds.